Great “Space Weather Events” in March 1653 and September 1672 Were Not Supported With Simultaneous/Clustering Auroral Observations During the Maunder Minimum - Hattori, Kentaro; Hayakawa, Hisashi; Ebihara, Yusuke (Frontiers in Astronomy and Space Sciences, 2022)
The solar activity has been significantly weakened during the Maunder Minimum (MM: 1645 – 1715), whereas little has been commonly agreed on the actual solar-activity magnitude and the space weather activity in this interval. Here, the East Asian records provide unique references for the low-latitude aurorae in the MM, particularly with the (quasi-)simultaneous candidate auroral accounts in March 1653 and September 1672. These cases have formed unique cases for the intense space weather events and solar-terrestrial interactions in the MM. In particular, the former has been regarded as ‘virtually incontrovertible evidence’ for an intense geomagnetic storm in the Maunder Minimum, despite significant suppression of the solar activity therein. Thus, this record has attracted scientific interpretations on the physical mechanism. However, our philological analyses have traced these source records further back to their original sources and have detected chronological problems in the Japanese source documents. For the 1653 March event, we have identified that the Japanese record retrospectively referred to a hearsay report between 31 December 1652 and 28 January 1653, instead of one on 2 March 1653. Our modification has been verified in two additional contemporary records. In addition, we have further analysed the candidate auroral report of 21 September 1672, which has been subjected to the doubts on the chronological errors. Herein, we have consulted contemporary records and reinforced the revised date of 7 September 1635. Our philological study has cast serious caveats on the reliability of the (quasi-)simultaneous East Asian records for candidate aurorae during the Maunder Minimum, emphasised the importance of philological studies on the auroral records, and highlighted that further discussions are required on the solar–terrestrial environment in the grand solar minima.